Coordinated MT-s1, s2-Convex Functions and Their Integral Inequalities of Hermite–Hadamard Type. (29th April 2021) - Mei, Hua; Wan, Aying; Guo, Bai-Ni
Abstract : In the paper, the authors introduce a new concept of MT-s 1, s 2 -convex functions on the coordinates on the rectangle of the plane and establish some new Hermite–Hadamard-type inequalities for this kind of functions.